2023
DOI: 10.1007/s13246-023-01265-0
|View full text |Cite
|
Sign up to set email alerts
|

Radiomics analysis of bone marrow biopsy locations in [18F]FDG PET/CT images for measurable residual disease assessment in multiple myeloma

Eva Milara,
Rafael Alonso,
Lena Masseing
et al.

Abstract: The combination of visual assessment of whole body [18F]FDG PET images and evaluation of bone marrow samples by Multiparameter Flow Cytometry (MFC) or Next-Generation Sequencing (NGS) is currently the most common clinical practice for the detection of Measurable Residual Disease (MRD) in Multiple Myeloma (MM) patients. In this study, radiomic features extracted from the bone marrow biopsy locations are analyzed and compared to those extracted from the whole bone marrow in order to study the representativeness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…The PRISMA flowchart of the articles included in our review is reported in Figu The literature search identified a total of 31 studies. According to the aforementio eligibility criteria, 10 studies were included [17][18][19][20][21][22][23][24][25][26]. Among these, eight studies w retrospective and two prospective.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The PRISMA flowchart of the articles included in our review is reported in Figu The literature search identified a total of 31 studies. According to the aforementio eligibility criteria, 10 studies were included [17][18][19][20][21][22][23][24][25][26]. Among these, eight studies w retrospective and two prospective.…”
Section: Resultsmentioning
confidence: 99%
“…R-Sofware [17,19,22] and Python [22,25,26] were the most used AI open source programming languages for the endpoint prediction and statistical analysis. In addition, Orange [18,21] was the most used toolkit to build the predictive model. The main data-mining algorithms used to perform ML strategies were random forests, including their extension in random survival forest [17,18,20,21,23,25] and k-nearest neighbors [18,20,21,23,26].…”
Section: Radiomics Assessmentmentioning
confidence: 99%
See 3 more Smart Citations